The struggle against dogmatism Wittgenstein and the concept of philosophy - Kuusela, Oskari (Harvard University Press, 2008)
Searching for rigor and a clear grasp of the essential features of their objects of investigation, philosophers are often driven to exaggerations and harmful simplifications. According to Ludwig Wittgenstein's provocative suggestion, this has to do with confusions relating to the status of philosophical statements. The Struggle against Dogmatism elucidates his view that there are no theses, doctrines, or theories in philosophy. Even when this claim is taken seriously, explanations of what it means are problematic--typically involving a relapse to theses. This book makes Wittgenstein's philosophical approach comprehensible by presenting it as a response to specific problems relating to the practice of philosophy, in particular the problem of dogmatism. Although the focus of this book is on Wittgenstein's later work, Oskari Kuusela also discusses Wittgenstein's early philosophy as expressed in the Tractatus, as well as the relation between his early and later work. In the light of this account of Wittgenstein's critique of his early thought, Kuusela is able to render concrete what Wittgenstein means by philosophizing without theses or theories. In his later philosophy, Kuusela argues, Wittgenstein establishes a non-metaphysical (though not anti-metaphysical) approach to philosophy without philosophical hierarchies. This method leads to an increase in the flexibility of philosophical thought without a loss in rigor.